Fiqih Al-Aqalliyyat dalam Perspektif Wasathiyyah: Analisis Pemikiran Abdullah bin Bayyah - Lola Yuanda Arlinza; Moh Khusen; Saskia Afridah; Suke Indah Khumaero (Journal of Sharia and Legal Science, 2025)
This study aims to analyze in depth the concept of fiqh al-aqalliyyat from the perspective of wasathiyyah based on the thought of Abdullah bin Bayyah, as well as explain the contribution of this concept to the development of minority Muslim fiqh today. The focus of the research is on the methodological aspect in the formation of Islamic law for minority Muslim communities who often face conflicts between the normative provisions of sharia and modern social conditions. This study uses a qualitative approach with normative and conceptual analysis methods of the main work of Abdullah bin Bayyah as a primary data source, supported by various jurisprudence literature and contemporary Islamic thought. The findings of the study show that there is a pattern of legal thinking that emphasizes maqāṣid al-syarī'ah, the principle of maslahat, and the value of moderation (wasathiyyah) as the main framework in Fiqh al-Aqalliyyat. The conclusion of the study underlines that the added value of this study lies in the systematic elaboration of the relationship between wasathiyyah and Fiqh al-Aqalliyyat, which has not been explicitly explained in previous research.